Multiaxial fatigue analysis for IMIC of ITER upper ELM coil - Zhang, S.W.; Song, Y.T.; Wang, Z.W.; Lu, S.; Ji, X.; Du, S.S.; Liu, X.F.; Feng, C.L.; Yang, H.; Wang, S.K.; Luo, Z.R. (Fusion engineering and design, 2014)
•The structural analysis provides the initial stresses.•Constant and variation of principal stress direction provide the design codes.•Two methods can be recommended for the ELM coils.•IMIC meets the fatigue criteria. Inconel Jacketed Mineral Insulated Conductor (IMIC) is a very important component of International Thermonuclear Experimental Reactor (ITER) Edge Localized Modes (ELM) coils, which are located between the vacuum vessel (VV) and blanket shield modules and subject to high radiation levels, high temperature and high magnetic field. These coils will experience thermal pulsed, cyclic electromagnetic (EM) load during operation. They are designed to sustain at 1.5e8 total stress cycles and shall have sufficient strength and excellent fatigue to transport and bear the high cyclic load. For IMIC, multiaxial fatigue analysis is used to evaluate failure. Two methods based on the alternating stress and mean stress in American Society of Mechanical Engineers (ASME) code provide the design codes for multiaxial fatigue evaluation: constant principal stress direction and variation of principal stress direction. Results show that using the two methods obtains basically the same equivalent alternating stress. Both of them can be recommended for the ELM coils and IMIC can meet the fatigue criteria.